Achyut Bharadwaj, Saee Patil, Valentio Iverson, Danny Li August 2021 Acknowledgements
# This work was carried out as part of a research project at PROMYS-2021 . I am a grateful recipient of the Mehta Fellowship to the PROMYS programs in 2021 and 2022.
Preliminary Definitions
# Finding Patterns
# (1) 1 , 4 , 7 , 10 , ⋯ ? 1,4,7,10,\cdots\;\;? 1 , 4 , 7 , 10 , ⋯ ? Here’s a harder one:
(2) 3 , 4 , 6 , 9 , 13 , ⋯ ? 3,4,6,9,13,\cdots\;\;? 3 , 4 , 6 , 9 , 13 , ⋯ ?
Notations
# (3) Δ ( f ) ( x ) = f ( x + 1 ) − f ( x ) \Delta\left(f\right)(x)=f(x+1)-f(x) Δ ( f ) ( x ) = f ( x + 1 ) − f ( x ) (4) Δ n + 1 ( f ) = Δ ( Δ n ( f ) ) \Delta^{n+1}(f)=\Delta\left(\Delta^n(f)\right) Δ n + 1 ( f ) = Δ ( Δ n ( f ) ) What is Δ ( f ) \Delta\left(f\right) Δ ( f ) when f f f is 1 , 4 , 7 , 10 , ⋯ 1,4,7,10,\cdots 1 , 4 , 7 , 10 , ⋯ ?
What is Δ ( f ) \Delta\left(f\right) Δ ( f ) when f f f is 3 , 4 , 6 , 9 , 13 ⋯ 3,4,6,9,13\cdots 3 , 4 , 6 , 9 , 13 ⋯ ?
What is Δ 2 ( f ) \Delta^2(f) Δ 2 ( f ) when f f f is 3 , 4 , 6 , 9 , 13 ⋯ 3,4,6,9,13\cdots 3 , 4 , 6 , 9 , 13 ⋯ ?
Some Results
# Δ ( f ) \Delta\left(f\right) Δ ( f ) is a polynomial iff f f f is a polynomial.
(5) Δ n ( f ) = c ⇒ Δ n + 1 ( f ) = 0 \Delta^n(f)=c\Rightarrow \Delta^{n+1}(f)=0 Δ n ( f ) = c ⇒ Δ n + 1 ( f ) = 0 Let
(6) f ( x ) = a m x m + a m − 1 x m − 1 + ⋯ + a 1 x + a 0 , a m ≠ 0 f(x)=a_mx^m+a_{m-1}x^{m-1}+\cdots+a_1x+a_0,a_m\neq0 f ( x ) = a m x m + a m − 1 x m − 1 + ⋯ + a 1 x + a 0 , a m = 0 The least n n n such that Δ n ( f ) = 0 \Delta^n(f)=0 Δ n ( f ) = 0 is m + 1 m+1 m + 1 .
Δ − 1 \Delta^{-1} Δ − 1
# We define Δ − 1 ( f ( x ) ) \Delta^{-1}(f(x)) Δ − 1 ( f ( x )) as a function g ( x ) g(x) g ( x ) such
that Δ ( g ( x ) ) = f ( x ) \Delta\left(g(x)\right) = f(x) Δ ( g ( x ) ) = f ( x ) .
Patterns again!
#
(7) 1 2 + 2 2 + 3 2 + ⋯ + ( n − 1 ) 2 = ? 1^2 + 2^2 + 3^2 + \cdots + (n-1)^2 = ~? 1 2 + 2 2 + 3 2 + ⋯ + ( n − 1 ) 2 = ? What about(8) 1 3 + 2 3 + ⋯ + ( n − 1 ) 3 = ? 1^3 + 2^3 + \cdots + (n-1)^3 = ~? 1 3 + 2 3 + ⋯ + ( n − 1 ) 3 = ? Can you find(9) ∑ i = 0 n − 1 i k \sum_{i=0}^{n-1} i^k i = 0 ∑ n − 1 i k recursively?
Generalizing
# Observe that
(10) ∑ i = 0 n − 1 ( i + 1 ) k − ∑ i = 0 n − 1 i k = n k \sum_{i=0}^{n-1}(i+1)^k - \sum_{i=0}^{n-1}i^k = n^k i = 0 ∑ n − 1 ( i + 1 ) k − i = 0 ∑ n − 1 i k = n k So,(11) ∑ i = 0 n − 1 ( i + 1 ) k − i k = n k \sum_{i=0}^{n-1}(i+1)^k - i^k = n^k i = 0 ∑ n − 1 ( i + 1 ) k − i k = n k
The above becomes:
(12) ∑ i = 0 n − 1 ∑ j = 1 k ( k j ) i k − j = ∑ i = 0 n − 1 ( k i k − 1 + ∑ j = 2 k ( k j ) i k − j ) = n k \sum_{i=0}^{n-1}\sum_{j=1}^{k}\binom{k}{j}i^{k-j} = \sum_{i=0}^{n-1}(ki^{k-1} + \sum_{j=2}^{k}\binom{k}{j}i^{k-j}) = n^k i = 0 ∑ n − 1 j = 1 ∑ k ( j k ) i k − j = i = 0 ∑ n − 1 ( k i k − 1 + j = 2 ∑ k ( j k ) i k − j ) = n k using the binomial theorem.
So, we have
(13) n k − ∑ i = 0 n − 1 ( ∑ j = 2 k ( k j ) i k − j ) = k ∑ i = 0 n − 1 i k n^k-\sum_{i=0}^{n-1}(\sum_{j=2}^{k}\binom{k}{j}i^{k-j}) = k\sum_{i=0}^{n-1}i^{k} n k − i = 0 ∑ n − 1 ( j = 2 ∑ k ( j k ) i k − j ) = k i = 0 ∑ n − 1 i k by rearranging the above.
Hence,
(14) ∑ i = 0 n − 1 i k = n k − ∑ i = 0 n − 1 ( ∑ j = 2 k ( ( k j ) i k − j ) ) k \sum_{i=0}^{n-1}i^k = \frac{n^k - \sum_{i=0}^{n-1}(\sum_{j=2}^{k}(\binom{k}{j}i^{k-j}))}{k} i = 0 ∑ n − 1 i k = k n k − ∑ i = 0 n − 1 ( ∑ j = 2 k ( ( j k ) i k − j ))
Calculus vs Finite Differences
# Addition and multiplication under a finite difference
# (15) Δ ( f ( x ) + g ( x ) ) = Δ ( f ( x ) ) + Δ ( g ( x ) ) \Delta\left(f(x)+g(x)\right) = \Delta\left(f(x)\right)+\Delta\left(g(x)\right) Δ ( f ( x ) + g ( x ) ) = Δ ( f ( x ) ) + Δ ( g ( x ) ) (16) Δ ( f ( x ) + g ( x ) ) = ( f ( x + 1 ) + g ( x + 1 ) ) − ( f ( x ) + g ( x ) ) = ( f ( x + 1 ) − f ( x ) ) + g ( x + 1 ) − g ( x ) = Δ ( f ( x ) ) + Δ ( g ( x ) ) \begin{aligned}\Delta\left(f(x)+g(x)\right) &= (f(x+1)+g(x+1)) - (f(x)+g(x)) \\ &= (f(x+1)-f(x)) + g(x+1) - g(x) \\ &= \Delta\left(f(x)\right) + \Delta\left(g(x)\right)\end{aligned} Δ ( f ( x ) + g ( x ) ) = ( f ( x + 1 ) + g ( x + 1 )) − ( f ( x ) + g ( x )) = ( f ( x + 1 ) − f ( x )) + g ( x + 1 ) − g ( x ) = Δ ( f ( x ) ) + Δ ( g ( x ) ) Multiplication of finite difference
# We now try to find a generic formula
for the product of two functions under a finite difference.
(17) Δ ( f ( x ) ⋅ g ( x ) ) = f ( x + 1 ) Δ ( g ( x ) ) + g ( x ) Δ ( f ( x ) ) \Delta\left(f(x)\cdot g(x)\right) = f(x+1)\Delta\left(g(x)\right) + g(x)\Delta\left(f(x)\right) Δ ( f ( x ) ⋅ g ( x ) ) = f ( x + 1 ) Δ ( g ( x ) ) + g ( x ) Δ ( f ( x ) )
(18) Δ ( f ( x ) ⋅ g ( x ) ) = f ( x + 1 ) g ( x + 1 ) − f ( x ) g ( x ) \Delta\left(f(x)\cdot g(x)\right) = f(x+1)g(x+1) - f(x)g(x) Δ ( f ( x ) ⋅ g ( x ) ) = f ( x + 1 ) g ( x + 1 ) − f ( x ) g ( x ) We add and subtract g ( x ) f ( x + 1 ) g(x)f(x+1) g ( x ) f ( x + 1 ) in the above to get:(19) Δ ( f ⋅ g ) = f ( x + 1 ) g ( x + 1 ) − f ( x ) g ( x ) + f ( x + 1 ) g ( x ) − f ( x + 1 ) g ( x ) = f ( x + 1 ) ( g ( x + 1 ) − g ( x ) ) + g ( x ) ( f ( x + 1 ) − f ( x ) ) = f ( x + 1 ) Δ ( g ( x ) ) + g ( x ) Δ ( f ( x ) ) \begin{aligned} \Delta\left(f\cdot g\right) &= f(x+1)g(x+1) - f(x)g(x) + f(x+1)g(x) - f(x+1)g(x) \\ &= f(x+1)(g(x+1) - g(x)) + g(x)(f(x+1)-f(x)) \\ &= f(x+1)\Delta\left(g(x)\right) + g(x)\Delta\left(f(x)\right) \end{aligned} Δ ( f ⋅ g ) = f ( x + 1 ) g ( x + 1 ) − f ( x ) g ( x ) + f ( x + 1 ) g ( x ) − f ( x + 1 ) g ( x ) = f ( x + 1 ) ( g ( x + 1 ) − g ( x )) + g ( x ) ( f ( x + 1 ) − f ( x )) = f ( x + 1 ) Δ ( g ( x ) ) + g ( x ) Δ ( f ( x ) )
Division under a finite difference
# Before trying to find a formula for
division, we try to find one for the multiplicative inverse, i.e.
finding Δ ( 1 f ( x ) ) \Delta\left(\frac{1}{f(x)}\right) Δ ( f ( x ) 1 ) in terms of f ( x ) f(x) f ( x )
(20) Δ ( 1 f ( x ) ) = 1 f ( x + 1 ) − 1 f ( x ) = f ( x ) − f ( x + 1 ) f ( x + 1 ) f ( x ) = − Δ ( f ( x ) ) f ( x + 1 ) f ( x ) \Delta\left(\frac{1}{f(x)}\right) = \frac{1}{f(x+1)} - \frac{1}{f(x)} = \frac{f(x)-f(x+1)}{f(x+1)f(x)} = -\frac{\Delta\left(f(x)\right)}{f(x+1)f(x)} Δ ( f ( x ) 1 ) = f ( x + 1 ) 1 − f ( x ) 1 = f ( x + 1 ) f ( x ) f ( x ) − f ( x + 1 ) = − f ( x + 1 ) f ( x ) Δ ( f ( x ) ) Now,(21) Δ ( f ( x ) g ( x ) ) = Δ ( f ( x ) ⋅ 1 g ( x ) ) = f ( x + 1 ) Δ ( 1 g ( x ) ) + 1 g ( x ) Δ ( f ( x ) ) \Delta\left(\frac{f(x)}{g(x)}\right) = \Delta\left(f(x)\cdot\frac{1}{g(x)}\right) = f(x+1)\Delta\left(\frac{1}{g(x)}\right) + \frac{1}{g(x)}\Delta\left(f(x)\right) Δ ( g ( x ) f ( x ) ) = Δ ( f ( x ) ⋅ g ( x ) 1 ) = f ( x + 1 ) Δ ( g ( x ) 1 ) + g ( x ) 1 Δ ( f ( x ) ) by the product formula.
The above can be written as:(22) − f ( x + 1 ) Δ ( g ( x ) ) g ( x + 1 ) g ( x ) + Δ ( f ( x ) ) g ( x ) = g ( x + 1 ) Δ ( f ( x ) ) − f ( x + 1 ) Δ ( g ( x ) ) g ( x + 1 ) g ( x ) -f(x+1)\frac{\Delta\left(g(x)\right)}{g(x+1)g(x)} + \frac{\Delta\left(f(x)\right)}{g(x)} = \frac{g(x+1)\Delta\left(f(x)\right)-f(x+1)\Delta\left(g(x)\right)}{g(x+1)g(x)} − f ( x + 1 ) g ( x + 1 ) g ( x ) Δ ( g ( x ) ) + g ( x ) Δ ( f ( x ) ) = g ( x + 1 ) g ( x ) g ( x + 1 ) Δ ( f ( x ) ) − f ( x + 1 ) Δ ( g ( x ) )
Chain Rule
# Evaluate Δ ( f ( x ) ) \Delta\left(f(x)\right) Δ ( f ( x ) ) when f ( x ) = ( 2 x ) 2 f(x)=(2x)^2 f ( x ) = ( 2 x ) 2
( 2 x ) 2 = 4 x 2 (2x)^2 = 4x^2 ( 2 x ) 2 = 4 x 2 . Now, Δ ( 4 x 2 ) = 4 Δ ( x 2 ) = 4 ( 2 x + 1 ) = 8 x + 4 \Delta\left(4x^2\right) = 4\Delta\left(x^2\right) = 4(2x+1) = 8x+4 Δ ( 4 x 2 ) = 4Δ ( x 2 ) = 4 ( 2 x + 1 ) = 8 x + 4 .
We compare this with the calculus chain rule. Is it possible to let
u = 2 x u=2x u = 2 x , find Δ ( f ( u ) ) \Delta\left(f(u)\right) Δ ( f ( u ) ) , and multiply it by Δ u \Delta u Δ u to get the
result as we do in calculus?
(23) f ( u ) = u 2 ⟹ Δ f ( u ) = 2 u + 1 = 4 x + 1 f(u)=u^2 \implies \Delta f(u) = 2u + 1 = 4x + 1 f ( u ) = u 2 ⟹ Δ f ( u ) = 2 u + 1 = 4 x + 1 Also, Δ u = 2 \Delta u = 2 Δ u = 2 .
So,(24) Δ f ( u ) ⋅ Δ u = ( 4 x + 1 ) × 2 = 8 x + 2 ≠ 8 x + 4 \Delta f(u)\cdot \Delta u = (4x+1)\times2 = 8x + 2 \neq 8x+4 Δ f ( u ) ⋅ Δ u = ( 4 x + 1 ) × 2 = 8 x + 2 = 8 x + 4 We
explore why it does not work in the next few slides.
We think of the function Δ \Delta Δ as finding the slope of a
curve between two integral points.
Fig-1:
Chain Rule So, we can conclude that
(25) Δ ( ( f ) ( x ) ) = Δ ( f ( x ) ) Δ x \Delta\left((f)(x)\right) = \frac{\Delta\left(f(x)\right)}{\Delta x} Δ ( ( f ) ( x ) ) = Δ x Δ ( f ( x ) )
We need
(26) Δ f Δ g ⋅ Δ g Δ x = f ( g ( x ) ) Δ ( g ( x ) ) \frac{\Delta f}{\Delta g}\cdot\frac{\Delta g}{\Delta x} = f(g(x))\Delta\left(g(x)\right) Δ g Δ f ⋅ Δ x Δ g = f ( g ( x )) Δ ( g ( x ) ) for the chain rule to work.
We know that
(27) Δ g ( x ) Δ x = Δ g ( x ) \frac{\Delta g(x)}{\Delta x} = \Delta g(x) Δ x Δ g ( x ) = Δ g ( x ) from the graph
in Fig-1 . Hence, we need(28) Δ f ( x ) Δ g ( x ) = f ( g ( x ) ) \frac{\Delta f(x)}{\Delta g(x)} = f(g(x)) Δ g ( x ) Δ f ( x ) = f ( g ( x )) for the chain rule to work.
This however does not hold true for every f ( x ) , g ( x ) f(x),g(x) f ( x ) , g ( x ) as we saw in the
example.
In calculus however, the difference is not finite. Hence, the above
holds.
Some fun with Δ − 1 \Delta^{-1} Δ − 1
# Find Δ − 1 ( x + 1 ) \Delta^{-1}(x + 1) Δ − 1 ( x + 1 ) . Can you find Δ − 1 ( f ( x ) + g ( x ) ) \Delta^{-1}(f(x)+g(x)) Δ − 1 ( f ( x ) + g ( x )) in
terms of f ( x ) , g ( x ) f(x),g(x) f ( x ) , g ( x ) ?
We know
(29) Δ − 1 ( 2 x + 1 ) = x 2 + c \Delta^{-1}(2x+1) = x^2+c Δ − 1 ( 2 x + 1 ) = x 2 + c . Also,(30) Δ − 1 x = x 2 − x 2 + c \Delta^{-1}x = \frac{x^2-x}{2}+c Δ − 1 x = 2 x 2 − x + c So, one can guess that(31) Δ − 1 ( 2 x + 1 ) = x 2 − x 2 − x 2 = x 2 + x 2 + c \Delta^{-1}(2x+1) = x^2 - \frac{x^2-x}{2} = \frac{x^2 + x}{2}+c Δ − 1 ( 2 x + 1 ) = x 2 − 2 x 2 − x = 2 x 2 + x + c for
some constant c c c . Indeed, we can check to see that this is true!
Notice that this is the same as(32) Δ − 1 ( x ) + Δ − 1 ( 1 ) \Delta^{-1}(x) + \Delta^{-1}(1) Δ − 1 ( x ) + Δ − 1 ( 1 ) This
leads to a proposition.
Addition under Δ − 1 \Delta^{-1} Δ − 1
#
(33) Δ − 1 ( f + g ) = Δ − 1 ( f ) + Δ − 1 ( g ) \Delta^{-1}(f+g) = \Delta^{-1}(f)+\Delta^{-1}(g) Δ − 1 ( f + g ) = Δ − 1 ( f ) + Δ − 1 ( g ) for all f , g f,g f , g whose
differences are defined.
We know that
(34) Δ ( f ′ + g ′ ) = Δ ( f ′ ) + Δ ( g ′ ) \Delta\left(f'+g'\right) = \Delta\left(f'\right)+\Delta\left(g'\right) Δ ( f ′ + g ′ ) = Δ ( f ′ ) + Δ ( g ′ ) Now,(35) Δ − 1 ( Δ ( f ′ + g ′ ) ) = f ′ + g ′ \Delta^{-1}(\Delta\left(f'+g'\right)) = f'+g' Δ − 1 ( Δ ( f ′ + g ′ ) ) = f ′ + g ′ Hence,(36) Δ − 1 ( Δ ( f ′ ) + Δ ( g ′ ) ) = f ′ + g ′ \Delta^{-1}(\Delta\left(f'\right)+\Delta\left(g'\right))=f'+g' Δ − 1 ( Δ ( f ′ ) + Δ ( g ′ ) ) = f ′ + g ′
Also,
(37) Δ − 1 ( Δ ( f ′ ) ) + Δ − 1 ( Δ ( g ′ ) ) = f ′ + g ′ \Delta^{-1}(\Delta\left(f'\right)) + \Delta^{-1}(\Delta\left(g'\right)) = f' + g' Δ − 1 ( Δ ( f ′ ) ) + Δ − 1 ( Δ ( g ′ ) ) = f ′ + g ′
Equating the LHS of the above two equations, we get:
(38) Δ − 1 ( Δ ( f ′ ) + Δ ( g ′ ) ) = Δ − 1 ( Δ ( f ′ ) ) + Δ − 1 ( Δ ( g ′ ) ) \Delta^{-1}(\Delta\left(f'\right)+\Delta\left(g'\right))=\Delta^{-1}(\Delta\left(f'\right)) + \Delta^{-1}(\Delta\left(g'\right)) Δ − 1 ( Δ ( f ′ ) + Δ ( g ′ ) ) = Δ − 1 ( Δ ( f ′ ) ) + Δ − 1 ( Δ ( g ′ ) ) We let(39) Δ ( f ′ ) = f , Δ ( g ′ ) = g \Delta\left(f'\right) = f, \Delta\left(g'\right) = g Δ ( f ′ ) = f , Δ ( g ′ ) = g Thus,(40) Δ − 1 ( f + g ) = Δ − 1 ( f ) + Δ − 1 ( g ) \Delta^{-1}(f+g) = \Delta^{-1}(f)+\Delta^{-1}(g) Δ − 1 ( f + g ) = Δ − 1 ( f ) + Δ − 1 ( g ) for all f , g f,g f , g given
that f ’ , g ’ f’,g’ f ’ , g ’ exist. That is, f f f and g g g must have defined differences.
Generalizing
# A motivating question
# We are interested in the following question.
Can we find a polynomial that fits a certain given data?
Let us consider the following example. Can we find a quadratic
polynomial f f f such that
(41) f ( 0 ) = 1 , f ( 1 ) = 0 , f ( 2 ) = 5 , f ( 3 ) = − 1 ? f(0) = 1, f(1) = 0, f(2) = 5, f(3) = -1~? f ( 0 ) = 1 , f ( 1 ) = 0 , f ( 2 ) = 5 , f ( 3 ) = − 1 ?
A motivating question indeed, and the answer is no . Suppose there exists
such quadratic polynomial f f f , then
(42) Δ 3 f ( x ) = 0 , ∀ x ∈ R \Delta^3 f(x) = 0, \forall x \in \mathbb{R} Δ 3 f ( x ) = 0 , ∀ x ∈ R However, we can check
that(43) Δ 3 f ( 0 ) = f ( 3 ) − 3 f ( 2 ) + 3 f ( 1 ) − f ( 0 ) = − 17 \Delta^3 f(0) = f(3) - 3f(2) + 3f(1) - f(0) = -17 Δ 3 f ( 0 ) = f ( 3 ) − 3 f ( 2 ) + 3 f ( 1 ) − f ( 0 ) = − 17
Consider a variant of the question before:
Can we find a cubic polynomial f f f such that
(44) f ( 0 ) = 1 , f ( 1 ) = 0 , f ( 2 ) = 5 , f ( 3 ) = − 1 ? f(0) = 1, f(1) = 0, f(2) = 5, f(3) = -1~? f ( 0 ) = 1 , f ( 1 ) = 0 , f ( 2 ) = 5 , f ( 3 ) = − 1 ? The answer is yes! The polynomial(45) − 17 6 x 3 + 23 2 x 2 − 29 3 x + 1 -\frac{17}{6}x^3+\frac{23}{2}x^2 - \frac{29}{3}x + 1 − 6 17 x 3 + 2 23 x 2 − 3 29 x + 1 works. But how
do we find this polynomial?
Since
(46) Δ ( Δ 2 ( f ( x ) ) ) = − 17 \Delta\left(\Delta^2(f(x))\right) = -17 Δ ( Δ 2 ( f ( x )) ) = − 17 (47) Δ 2 ( f ( x ) ) = − 17 x + c \Delta^2(f(x)) = -17x + c Δ 2 ( f ( x )) = − 17 x + c for some constant c c c . When x = 0 x=0 x = 0 ,(48) Δ 2 ( f ( x ) ) = 6 \Delta^2(f(x)) = 6 Δ 2 ( f ( x )) = 6 Hence, c = 6 c=6 c = 6 . Similarly,(49) Δ 2 ( f ( x ) ) = − 17 x + 6 ⟹ Δ ( f ( x ) ) = − 17 2 x 2 + 29 2 x + c ′ \Delta^2(f(x)) = -17x+6 \implies \Delta\left(f(x)\right) = -\frac{17}{2}x^2 + \frac{29}{2}x + c' Δ 2 ( f ( x )) = − 17 x + 6 ⟹ Δ ( f ( x ) ) = − 2 17 x 2 + 2 29 x + c ′ for some constant c ’ c’ c ’ . When x = 0 x=0 x = 0 , Δ ( f ( x ) ) = − 1 \Delta\left(f(x)\right) = -1 Δ ( f ( x ) ) = − 1 . Hence,
c ’ = − 1 c’ = -1 c ’ = − 1 . We could check that(50) Δ ( f ( x ) ) = 17 2 x 2 + 29 12 x − 1 \Delta\left(f(x)\right) = \frac{17}{2}x^2 + \frac{29}{12}x - 1 Δ ( f ( x ) ) = 2 17 x 2 + 12 29 x − 1 , which implies(51) f ( x ) = − 17 6 x 3 + 23 2 x 2 − 29 3 x + c ′ ′ f(x) = -\frac{17}{6}x^3 + \frac{23}{2}x^2 - \frac{29}{3}x + c'' f ( x ) = − 6 17 x 3 + 2 23 x 2 − 3 29 x + c ′′ When
x = 0 x=0 x = 0 , f ( x ) = 1 f(x) = 1 f ( x ) = 1 . Hence, c ’’ = 1 c’’=1 c ’’ = 1 . Thus, the cubic polynomial that fits
the given data is(52) − 17 6 x 3 + 23 2 x 2 − 29 3 x + 1 -\frac{17}{6}x^3+\frac{23}{2}x^2 - \frac{29}{3}x + 1 − 6 17 x 3 + 2 23 x 2 − 3 29 x + 1
Can we generalize this? Therefore, we began to ask the following
interesting question:
Given the values of f ( 0 ) , f ( 1 ) , … , f ( n ) f(0), f(1), \dots, f(n) f ( 0 ) , f ( 1 ) , … , f ( n ) , can we find a polynomial
f f f of degree not greater than n n n that fits this data? Is this
polynomial unique?
And the answer is yes to both questions.
Finding a polynomial that passes through n n n points
# Claim. For any
n , k , i ≤ k n,k, i \le k n , k , i ≤ k , we have
(53) Δ i ( n + k k ) = ( n + k k − i ) \Delta^i \binom{n + k}{k} = \binom{n + k}{k - i} Δ i ( k n + k ) = ( k − i n + k )
We will prove this by induction on i i i . Indeed, this is true for
i = 1 i = 1 i = 1 , since
(54) Δ ( n + k k ) = ( n + k + 1 k ) − ( n + k k ) = ( n + k k − 1 ) \Delta \binom{n + k}{k} = \binom{n +k + 1}{k} - \binom{n + k}{k} = \binom{n + k}{k - 1} Δ ( k n + k ) = ( k n + k + 1 ) − ( k n + k ) = ( k − 1 n + k ) Now,
fix n , k n,k n , k . Suppose this result is true for i = ℓ < k i = \ell < k i = ℓ < k , Then we will
prove that this is true for i = ℓ + 1 i = \ell + 1 i = ℓ + 1 .
Indeed,
(55) Δ ℓ + 1 ( n + k k ) = Δ ( Δ ℓ ( n + k k ) ) = Δ ( n + k k − ℓ ) = ( n + 1 + k k − ℓ ) − ( n + k k − ℓ ) = ( n + k k − ℓ − 1 ) \begin{aligned} \Delta^{\ell + 1} \binom{n + k}{k} &= \Delta \left( \Delta^{\ell} \binom{n + k}{k} \right) \\ &= \Delta \binom{n + k}{k - \ell} \\ &= \binom{n + 1 + k}{ k - \ell} - \binom{n + k}{k - \ell} \\ &= \binom{n + k}{k - \ell - 1} \end{aligned} Δ ℓ + 1 ( k n + k ) = Δ ( Δ ℓ ( k n + k ) ) = Δ ( k − ℓ n + k ) = ( k − ℓ n + 1 + k ) − ( k − ℓ n + k ) = ( k − ℓ − 1 n + k ) which proves our assertion.
Every polynomial P ( x ) P(x) P ( x ) can be uniquely represented as
(56) ∑ k a k ( n + k k ) \sum_{k} a_k \binom{n + k}{k} k ∑ a k ( k n + k ) for reals a k a_k a k .
Using this fact, note that if P ( x ) ≠ 0 P(x) \not= 0 P ( x ) = 0 , then
(57) Δ − 1 ( P ( x ) ) = ∑ k a k Δ − 1 ( ( n + k k ) ) = ∑ k a k ( n + k k + 1 ) \begin{aligned} \Delta^{-1}(P(x)) &= \sum_k a_k \Delta^{-1} \left( \binom{n + k}{k} \right) = \sum_k a_k \binom{n + k}{k + 1}\end{aligned} Δ − 1 ( P ( x )) = k ∑ a k Δ − 1 ( ( k n + k ) ) = k ∑ a k ( k + 1 n + k )
The previous argument
proves the existence of such a polynomial passing through
f ( 0 ) , f ( 1 ) , f ( 2 ) , … , f ( n ) f(0), f(1), f(2), \dots, f(n) f ( 0 ) , f ( 1 ) , f ( 2 ) , … , f ( n ) , ensuring the degree is not greater than
n n n .
In fact, we claim an even more generalized result.
Let x 1 , x 2 , … , x n x_1, x_2, \dots, x_n x 1 , x 2 , … , x n be n n n distinct real values and
y 1 , y 2 , … , y n y_1, y_2, \dots, y_n y 1 , y 2 , … , y n be n n n real numbers. Then there exists a unique
polynomial f ∈ R [ x ] f \in \mathbb{R}[x] f ∈ R [ x ] of degree less than n n n such that
f ( x i ) = y i f(x_i) = y_i f ( x i ) = y i for 1 ≤ i ≤ n 1 \le i \le n 1 ≤ i ≤ n .
Proof
# Proof. We’ll first prove that there exists such polynomial.
Consider the polynomial
(58) f ( x ) = ∑ i = 1 n y i ⋅ ∏ i ≠ j x − x j x i − x j f(x) = \sum_{i = 1}^n y_i \cdot \prod_{i \not= j} \frac{x - x_j}{x_i - x_j} f ( x ) = i = 1 ∑ n y i ⋅ i = j ∏ x i − x j x − x j Now, check that f ( x i ) = y i f(x_i) = y_i f ( x i ) = y i for every 1 ≤ i ≤ n 1 \le i \le n 1 ≤ i ≤ n , and we are
done. Finally, we will prove uniqueness. Indeed, if there exists two
working polynomials Q , R Q,R Q , R such that(59) Q ( x i ) = R ( x i ) = y i Q(x_i) = R(x_i) = y_i Q ( x i ) = R ( x i ) = y i for
1 ≤ i ≤ n 1 \le i \le n 1 ≤ i ≤ n . Then, either Q − R = 0 Q - R = 0 Q − R = 0 , or deg ( Q − R ) < n \text{deg} (Q - R) < n deg ( Q − R ) < n .
However, if Q − R ≠ 0 Q - R \not= 0 Q − R = 0 , the polynomial Q − R Q - R Q − R vanishes at n n n
points, with degree less than n n n , which is a contradiction.